2004
DOI: 10.1111/j.1440-1681.2004.04020.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response of Ropivacaine Administered Caudally to Children Undergoing Surgical Procedures Under Sedation With Midazolam

Abstract: 1. In a double-blind randomized controlled design, 50 children were allocated to receive bupivacaine 0.25% or ropivacaine 0.25%, 0.32%, 0.40% or 0.50% by caudal block. 2. Caudal block was performed after induction of anaesthesia with 2-5% sevoflurane, atropine 10 microg/kg and midazolam 100-300 microg/kg. During the surgical procedure, patients were maintained under spontaneous ventilation and no intravenous or inhalatory anaesthetic agent was administered. For transoperative sedation, midazolam 100-300 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this group the postoperative pain management provided adequate analgesia and was well tolerated [15 ]. Ropivacaine 0.25% administered in children through the caudal route for various surgical procedures produced at least 24 h of postoperative analgesia [16]. For continuous peripheral nerve blocks (axillary, femoral and sciatic for major orthopedic surgery and trauma) a bolus dose of 0.5-1 ml kg À1 (depending on the nerve to be blocked) of ropivacaine 0.2% with clonidine 2 mg kg À1 has been used.…”
Section: Ropivacainementioning
confidence: 98%
“…In this group the postoperative pain management provided adequate analgesia and was well tolerated [15 ]. Ropivacaine 0.25% administered in children through the caudal route for various surgical procedures produced at least 24 h of postoperative analgesia [16]. For continuous peripheral nerve blocks (axillary, femoral and sciatic for major orthopedic surgery and trauma) a bolus dose of 0.5-1 ml kg À1 (depending on the nerve to be blocked) of ropivacaine 0.2% with clonidine 2 mg kg À1 has been used.…”
Section: Ropivacainementioning
confidence: 98%
“…Seventeen such RCTs were reviewed in detail using a structured methodology. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Two review articles were also identified. 18,19 The reference lists for all of these 19 publications were reviewed to identify any further RCTs that may have been missed with the initial search strategy; no such study was found.…”
Section: Methodsmentioning
confidence: 99%